2007
DOI: 10.1007/s10194-007-0423-6
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of a Georgian language headache questionnaire in a population-based sample

Abstract: In a pilot phase of a survey of the prevalence of primary headache disorders in the Republic of Georgia, we validated a Georgian language questionnaire for migraine (MIG), tension-type headache (TTH), MIG+TTH and trigeminal autonomic cephalalgias (TAC). A population-based sample of 186 people with headache completed the questionnaire and were blindly examined by one of two headache experts. The questionnaire diagnoses were: MIG 49, TTH 76, MIG+TTH 45 and TAC 16. The physicians’diagnoses were: MIG 59, TTH 77, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
0
20
1
Order By: Relevance
“…The questionnaire showed a 100% sensitivity and a specificity of 93.3% for migraine without aura and of 100% for frequent episodic tension‐type headache, which were the most common headache types in our study population. Sensitivity and specificity were also high for the other headache types detected in this population and were higher than those found in recent validation studies 32,33,37 . Kukava et al, 33 for example, reported that the sensitivity and specificity of the questionnaire were 75% and 96% for migraine and 79% and 86% for tension‐type headache, respectively.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…The questionnaire showed a 100% sensitivity and a specificity of 93.3% for migraine without aura and of 100% for frequent episodic tension‐type headache, which were the most common headache types in our study population. Sensitivity and specificity were also high for the other headache types detected in this population and were higher than those found in recent validation studies 32,33,37 . Kukava et al, 33 for example, reported that the sensitivity and specificity of the questionnaire were 75% and 96% for migraine and 79% and 86% for tension‐type headache, respectively.…”
Section: Discussioncontrasting
confidence: 61%
“…15 Most questionnaires employed in epidemiological studies use diagnostic criteria from the ICHD-I classification of 1988. 7,16,17,19,[27][28][29][30] So far, few tools have been designed and validated according to the diagnostic criteria of the ICHD-II classification, [31][32][33][34][35][36][37] and no such tool exists in the Italian language.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The headache questionnaire of the German Headache Consortium was validated in Germany both in patients of the headache centre and in a population-based sample [18,19]. The same questionnaire, translated into The burden of headache in Russia the Georgian language and validated in a populationbased sample in the Republic of Georgia, achieved better sensitivity and specificity values for MIG or TTH occurring separately, as opposed to concomitantly in the same respondent [20]. It is worth briefly reviewing the preliminary epidemiological data, as these are the first such results available from this very large country.…”
Section: Discussionmentioning
confidence: 99%
“…The exact types of TACs are not specified and therefore the number of diagnosed CH cases is unknown [54]. The same questionnaire developed by Fritsche et al was tested in a general population with headache by Yoon et al [55] and Kukava et al [56]. An analysis algorythm based on the ICHD criteria was used to diagnose different types of headaches, but the algorythm details were not provided [54].…”
Section: Screening Tools For Chmentioning
confidence: 99%